2022
DOI: 10.1097/j.pbj.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into the use of immune checkpoint inhibitors in gastric cancer

Abstract: Gastric cancer (GC) is the fifth most incident and the fourth deadliest cancer worldwide. GC is a heterogeneous disease from the histological and molecular standpoints. This malignancy is mostly diagnosed at advanced stages of the disease, where the available therapeutic interventions are not effective. The emergence of immunotherapy has transformed the landscape of cancer treatment, including GC, and currently immune checkpoint inhibitors have been approved for the treatment of patients with recurrent/metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
(280 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, in recent years, programmed cell death protein 1 (PD-1) or programmed death-ligand 1 (PD-L1) inhibitors have been used to manage advanced gastric cancer treatment. Unfortunately, clinical trials demonstrate that treatments with nivolumab and pembrolizumab (PD-1 inhibitors) or avelumab (PD-L1 inhibitor) show a response rate of 22–27% in terms of survival [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in recent years, programmed cell death protein 1 (PD-1) or programmed death-ligand 1 (PD-L1) inhibitors have been used to manage advanced gastric cancer treatment. Unfortunately, clinical trials demonstrate that treatments with nivolumab and pembrolizumab (PD-1 inhibitors) or avelumab (PD-L1 inhibitor) show a response rate of 22–27% in terms of survival [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, immune checkpoint inhibitors in locally advanced and metastatic gastric cancer patients act by mediating the blockage of the programmed cell death protein 1 (PD-1)/PD-L1 axis. They are preferred in standard chemotherapy-refractory cases or those who have been previously treated with two or more chemotherapeutic regimens [9].…”
Section: Introductionmentioning
confidence: 99%
“…Immune activation by immune checkpoint inhibitors seems to have a more durable clinical benefit than traditional chemotherapy in locally A/MGC and a lower incidence of adverse events [18,19]. The ATTRACTION-2 phase III clinical trials l assessed Nivolumab or placebo in metastatic gastric cancer patients and showed significant overall survival that persisted over time [20].…”
Section: Introductionmentioning
confidence: 99%